TANTANGAN PENDIDIK DI ERA MILLENNIAL - Mahyuddin Barni (Transformatif, 2019)
Millennial or Generation Y is a group of people born after Generation X, namely people born in the range of 1980-2000. Now, this generation is between the ages of 17-37. There are some millennial students who have dropped out of school or graduated from universities and entered to work, but most of them are still in the school system.The image and concept of the teacher in contemporary society is very much different from the concept of the past. The past teacher means knowledgeable, wise, and prudent. Nowadays, teachers are seen as educational functionaries who are tasked with teaching on the basis of certain scientific and academic qualifications. With this task, the teacher receives material rewards from the state or the education manager. Thus, the most important factor in the teaching profession is scientific and academic qualifications. Meanwhile, wisdom and prudence which are moral attitudes and behaviors are no longer significant. In the classical concept, moral factors are above teacher qualifications.In general, teachers should understand the social changes that exist in the present. Teachers must not stop learning about new things. Global challenges in the current era are also different from the global challenges from the past. Whatever steps and methods carried out at school are certainly aimed at forming character and preparing quality human resources in Indonesia.In this paper, the author will outline the challenges for teachers in the millennial era and the efforts made in dealing with these challenges. Previously the author also explained about the millennial generation, and the professionalism of teachers.